2012
DOI: 10.1089/acm.2011.0428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biofield Therapy in the Human Brain

Abstract: Objectives: The effects of Okada Purifying Therapy (OPT), a form of subtle energy (biofield) therapy that originated in Japan, were investigated. Electroencephalograms and the Profile of Mood States scores were measured using a crossover design during OPT and placebo sessions. Participants: Nineteen (19) healthy Japanese adults (mean age -standard deviation: 40.8 -11.2 years; 10 females) with no previous experience of biofield therapy participated in this study. Methods: Each session lasted 15 minutes. A singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 9 publications
0
15
0
4
Order By: Relevance
“…The biofield treatment is an alternative strategy which is known to alter the properties of living and non-living materials. Biofield treatment is considered under complementary and alternative medicine and based on subtle energy field called biofield energy [10][11][12]. The human beings are infused with this precise form of energy.…”
Section: Introductionmentioning
confidence: 99%
“…The biofield treatment is an alternative strategy which is known to alter the properties of living and non-living materials. Biofield treatment is considered under complementary and alternative medicine and based on subtle energy field called biofield energy [10][11][12]. The human beings are infused with this precise form of energy.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was to search a cost-effective method for altering the properties of gerbera multiplication medium that can help in improving its functions. The biofield energy treatment is known worldwide for its healing therapies in stress, anxiety and pain related problems [10,11]. The energy medicines are considered by the National Centre for Complementary and Alternative Medicine (NCCAM)/National Institute of Health (NIH) under complementary and alternative medicines (CAM) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Biofield energy treatments are comprised of practices based on subtle energy field and generally it reflects the concept that human beings are infused with this form of energy [10]. It was shown that a unique bioenergetic field surrounds and permeates the human body [11].…”
Section: Introductionmentioning
confidence: 99%